Transcriptome profiling reveals differential expression of interferon family induced by dengue virus 2 in human endothelial cells on tissue culture plastic and polyacrylamide hydrogel. Issue 7 (12th January 2016) - Pei, Hua; Zuo, Li; Ma, Jing; Cui, Lili; Yu, Fangfang; Lin, Yingzi
Abstract : A cell model is critical for studying the molecular mechanisms of dengue virus 2 (DENV‐2) invasions and cell bioactivity can be easily affected by the substrate matrix. Tissue culture plastic (TCP) and polyacrylamide hydrogel (PAMH) are two kinds of matrices widely used for cells. The effects of different matrices on the cultured cells with DENV‐2 invasion remain unknown. To address the issue, the effects of TCP and PAMH were explored in primary human umbilical vein endothelial cells (HUVECs) with DENV‐2 invasion. HUVECs were assigned into four groups: group A (cultured on TCP), group B (cultured on PAMH), group C (cultured on TCP with DENV‐2 invasion), and group D (cultured on PAMH with DENV‐2 invasion). Flow cytometry was performed on HUVECs after 48‐hr culture. Gene expression patterns were analyzed by gene microarray. The levels of interleukin‐29 (IL‐29) were measured by real‐time qRT‐PCR and ELISA. There were no cell apoptosis induced by DENV‐2 in HUVECs cultured on TCP and PAMH ( P  > 0.05). After DENV‐2 invasion, the up‐regulated genes involve in the activities of oligoadenylate synthetase (OAS), interferon‐related cytokine, and growth factors so on. The up‐regulated pathways involve in the responses to DENV‐2 and innate immunity. IL‐29 was induced in the HUVECs on PAMH when compared with the cells on TCP ( P  < 0.05). Thus, different matrices cause different immune responses, which should be considered in the cell models for exploring the molecular mechanisms of DENV‐induced diseases. J. Med. Virol. 88:1137–1151, 2016 . © 2016 Wiley Periodicals, Inc.